A Correlational Study of Well-Being Psychology and Self Regulated Learning in Hafiz Student’s Learning Achievement in MA Tahfidzul Qur’an Isy Karima Karanganyar - Ahmad Zaky Romadlony; Mahsun Jayadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aimed to find out correlation between well-being psychology and self-regulated learning on student learning achievement of hafiz in MA Tahfidzul Qur'an Isy Karima Karanganyar". This study used quantitative method with multiple linear regression analysis. This study was a correlational research with data collection techniques in the form of psychology well-being and self-regulated learning scales. The learning achievement used grade point average (IPK / IPK). The subjects of this study were 30 hafiz students from a total of 150 hafiz students of the Tahfidzul Qur'an unit. Quota sampling technique was done by observing certain characteristics and SPSS for Windows 16.00 Version. The result showed that there was a correlation between well-being psychology and learning achievement obtained with correlation 0445 with significance 0,006 because of significance <0.05. Further, the correlation between self-regulated learning achievements showed the significance -0214 to 0128 as the significance> 0.05 so that it meant no correlation. The last correlation between well-being psychology and self-regulated learning obtained 0075 correlations with significance 0.347 as the significance> 0.05 so that it meant no correlation. Keywords: well-being psychology, self-regulated learning, learning achievement